Tourism and Algarve underwater archaeological heritage valorisation: a case study - Henriques, Cláudia Helena (2014)
This paper aims to investigate the interrelation between sea, tourism and culture associated with underwater archaeological heritage. Its main objective is to determine the existence of creative actions and projects that valorise tourism related with underwater archaeological heritage in the Algarve. The assumption is that underwater heritage is a valuable resource to tourism economy of seaside territories. Regarding the Algarve, WTTC (2003) refers that “the Travel & Tourism industry directly contributes 45% of GDP and 37% of jobs”. However, as is also refereed in this document “forecasts for the next ten years (2013) are very modest”. This means that, unless Algarve Tourism (Turismo do Algarve) and the private sector succeed in changing direction and surpassing the baseline forecasts, the share of visitor exports in the scheme of total exports will fall. As MEID/TP (2011) and Governo de Portugal (2013) point out for the Algarve region, the Sun and Sea, as well as Golf, are considered to be the main strategic products. The core Sun and Sea product should have a multi-segmented offer and be able to widen the summer season. In this context, it is important to develop new tourism products related with sea, nautical and cultural tourism. The present paper is based on a documental research of tourism public policies and also on a set of interviews of entities connected with underwater archaeological heritage with the intention of determining their role in the valorisation of this type of heritage in the Algarve.